Frustrated Spin Systems 2013
DOI: 10.1142/9789814440745_0009
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Spin Glasses

Abstract: We review recent findings on spin glass models. Both the equilibrium properties and the dynamic properties are covered. We focus on progress in theoretical, in particular numerical, studies, while its relationship to real magnetic materials is also mentioned.The motivation that pulls researchers toward spin glasses is possibly not the potential future use of spin glass materials in "practical" applications. It is rather the expectation that there must be something very fundamental in systems with randomness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 253 publications
(605 reference statements)
2
24
0
Order By: Relevance
“…The obtained location is consistent with a previous estimate such as 0.894(2), 9) and the obtained location is larger than but marginally consistent with 0.85 15) and 0.870, 21) while the obtained location is inconsistent with 0.896(2), 18) 0.86(2) 7) and 0.854(2). 20) As described above, the obtained locations of p (1) c and p (2) c are reasonably close to the previously estimated locations, although the approximate approach by regarding the present bonds as random bonds is applied. Thus, it is considered that this approximate approach is valid in this study.…”
Section: )supporting
confidence: 82%
See 4 more Smart Citations
“…The obtained location is consistent with a previous estimate such as 0.894(2), 9) and the obtained location is larger than but marginally consistent with 0.85 15) and 0.870, 21) while the obtained location is inconsistent with 0.896(2), 18) 0.86(2) 7) and 0.854(2). 20) As described above, the obtained locations of p (1) c and p (2) c are reasonably close to the previously estimated locations, although the approximate approach by regarding the present bonds as random bonds is applied. Thus, it is considered that this approximate approach is valid in this study.…”
Section: )supporting
confidence: 82%
“…We derive the lower bounds of the locations with no approximation by using the present bonds. The present bonds are slightly more complicated than the random bonds, so the exact values of P c with no approximation as 0.895 3995 · · · < p (1) c (no approximation) and 0.893 0756 · · · < p (2) c (no approximation). From one of these inequalities, it is shown that the present percolation and the plaquette percolation 7) yield different results, since the plaquette percolation gives p (2) c = 0.86(2).…”
Section: )mentioning
confidence: 95%
See 3 more Smart Citations